Antibody toolkit reveals N-terminally ubiquitinated substrates of UBE2W - Christopher W. Davies (Nature Portfolio, 2021)
UBE2W catalyzes the ubiquitination of protein N-termini but its substrate spectrum is largely unknown. Here, the authors discover mAbs selective for peptides derived from N-terminally ubiquitinated proteins, solve the structure of a peptide-bound mAb and apply the mAbs to map endogenous UBE2W substrates by proteomics.